THE UTILIZATION OF CONCRETE WASTE AS AN AGGREGATE SUBSTITUTE AND THE ADDITION OF DENIM FABRIC FIBERS ON COMPRESSIVE AND FLEXURAL STRENGTH OF CONCRETE : (AS AN IMPLEMENTATION OF CONCRETE TECHNOLOGY COURSE) - Farid Muhamad Harahap; Anisah Anisah; Ririt Aprilin (LPPM Universitas Negeri Jakarta, 2025)
Concrete is one of the construction materials used in building structures, bridges, roads, and others. The material components that make up concrete consist of fine aggregates (sand), coarse aggregates (gravel), water, and cement. However, the drawbacks of concrete include low tensile strength, heavy weight, high sound reflection, and difficulty in reshaping after it has been formed. Adding fibers is one way to increase the flexural strength of concrete. This study aims to determine the utilization of concrete waste and the addition of denim fabric fibers in improving the compressive strength and flexural strength of concrete, using fiber lengths of 100 mm and widths of 5 mm with variations of fiber addition at 1% and 2%. The test results at 28 days show the compressive strength values of control concrete, concrete with 1% fiber proportion, and 2% fiber proportion are 10,27 MPa, 8,3 MPa, and 5,44 MPa, respectively, with the optimum compressive strength being 10,27 MPa for the control concrete. Therefore, none of the compressive strengths reached the design compressive strength of 40 MPa. The flexural strength values from the tests are 3,52 MPa, 4,32 MPa, and 2,98 MPa, with the optimum flexural strength being 4,32 MPa at the 1% fiber proportion. The flexural strength values range between 34,27% to 54,77% of the compressive strength values.